Optical fiber sensors for challenging media - Novais, Susana Cristina Ribeiro (2020)
With the present work, the development of fiber optic sensor solutions for the application in challenging media was intended. New sensor structures based on the post-processing of optical fibers were addressed, taking into account their sensitivity to variations in the external environment. In a first stage, fiber Bragg gratings were embedded in lithium batteries, to monitor temperature in situ and operando. Due to the harsh chemical environment of the battery, fiber optic sensors revealed to be the most advantageous alternative, when comparing to the electronic sensors. Fiber sensors exhibited good sensitivities and fast responses, besides being less invasive, thus they did not compromise the battery response. Furthermore, they were chemically stable. Still in the framework of this theme, and with the objective of monitoring possible strain and pressure variations inside the batteries, new sensors based on in-line Fabry-Perot cavities have been proposed. These sensors were characterized in lateral load, strain, and temperature. In a later stage, the study focused on the development of configurations that allowed to obtain high-resolution and/or sensitivity sensors. One of such configurations was obtained by creating a hollow microsphere at the fiber tip. The sensor was used to detected concentration variations and refractive index of glycerin and water mixtures. The influence of the diaphragm size in the sensor response was also studied, as well as the temperature response. New sensors based on multimode interference have also been characterized, using a coreless silica fiber tip. First, the influence of different parameters, such as length and diameters were analyzed. The sensors were tested in different solutions of glucose and water. It was observed that the sensor diameter is a decisive factor in obtaining devices that are more sensitive to refractive index and, consequently, to concentration. The determination of the thermo-optic coefficient of water/ethanol mixtures was also addressed using a multimode fiber interferometer sensor. Finally, a multimode interferometer sensor was functionalized by depositing agarose throughout the structure, allowing to optimize the response of the sensors to the external environment.